Dualidade onda-partícula : uma sequência didática para o Ensino Médio com foco em atividades investigativas - Monico, Kleidiani Moreira (2018)
A few decades ago, the teaching of topics related to Modern and Contemporary Physics in High School played a secondary role and was often simply overlooked. However, we currently live in an increasingly globalized world where information circulates with great speed and scientific and technological advances are increasingly present in our daily. In this way, the content related to Modern and Contemporary Physics started to have an importance that maybe did not exist before, and the teaching of this content in High School started to have a mandatory character. In this context, we present in this work a proposal for the Teaching of Wave-Particle Duality content in an investigative perspective. Based on this perspective we constructed a teaching sequence, composed of conceptual support texts, activities and scripts for experimental demonstrations. The methodology used is based on investigative activities. To support our analysis, the data were processed through the application of a questionnaire, recordings of classes and a field diary. The sequence was applied in the first semester of 2018, in a class, with 35 students, from the second year of High School of the School State of Elementary and High School Aflordízio Carvalho da Silva, located in Vitória, Espírito Santo (ES). The research of quali-quanti nature, had as main objective to analyze the learning of the conceptual contents of the students. According to the results obtained, it is possible to perceive how the activities developed during the intervention have the potential to favor conceptual learning.